Makrouwarunkowania funkcjonowania regionalnych systemów innowacyjnych - doświadczenia międzynarodowe - Świadek, Arkadiusz (Macrodeterminants of Regional Innovation Systems Activity - International Evidences, 2006)
The answer for globalization process is regional innovation system (RIS). This is direction in theory and practice, whose aim is to create chances for small and medium enterprises for competitiveness with international firms. The concept of regional innovation system isn't autonomie, it exists in some specific environment. The fundamental aim in this case is to negotiate transparent and stable relation between RIS and national innovation system. Without clear conditions between these structures it is hard to expect success in the regional context. Hence world experience is a significant knowledge source by constructing RIS in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1099, s. 225-236